Computers as components : principles of embedded computing system design - Wolf, Marilyn, 1958- (Morgan Kaufmann series in computer architecture and design., 2022)
Computers as Components: Principles of Embedded Computing System Design, Fifth Edition continues to focus on foundational content in embedded systems technology and design while updating material throughout the book and introducing new content on machine learning and Internet-of-Things (IoT) systems.